ClbG in Avian Pathogenic Escherichia coli Contributes to Meningitis Development in a Mouse Model - Peili Wang; Jiaxiang Zhang; Yanfei Chen; Haoran Zhong; Heng Wang; Jianji Li; Guoqiang Zhu; Pengpeng Xia; Luying Cui; Jun Li; Junsheng Dong; Qingqing Gao; et al. (Toxins, 2021)
Colibactin is a complex secondary metabolite that leads to genotoxicity that interferes with the eukaryotic cell cycle. It plays an important role in many diseases, including neonatal mouse sepsis and meningitis. Avian pathogenic Escherichia coli (APEC) is responsible for several diseases in the poultry industry and may threaten human health due to its potential zoonosis. In this study, we confirmed that clbG was necessary for the APEC XM strain to produce colibactin. The deletion of clbG on APEC XM contributed to lowered γH2AX expression, no megalocytosis, and no cell cycle arrest in vitro. None of the 4-week Institute of Cancer Research mice infected with the APEC XM ΔclbG contracted meningitis or displayed weakened clinical symptoms. Fewer histopathological lesions were observed in the APEC XM ΔclbG group. The bacterial colonization of tissues and the relative expression of cytokines (IL-1β, IL-6, and TNF-α) in the brains decreased significantly in the APEC XM ΔclbG group compared to those in the APEC XM group. The tight junction proteins (claudin-5, occludin, and ZO-1) were not significantly destroyed in APEC XM ΔclbG group in vivo and in vitro. In conclusion, clbG is necessary for the synthesis of the genotoxin colibactin and affects the development of APEC meningitis in mice.